Kepuasan Konsumen, Kualitas Layanan, Celebrity Endorser, Dan Kepercayaan Merek Terhadap Minat Beli Ulang Pasta Gigi Pepsodent Di Yogya Mall Kabupaten Brebes - Alif Nurfitrah; Vivian Pushein Margaretha Amey; Roby Setiadi; Andi Yulianto; Nur Aisyah (CV. Aksara Global Akademia, 2023)
This study aims to analyze the effect of consumer satisfaction, service quality, celebrity endorsers, and brand trust on the interest in repurchasing Pepsodent toothpaste at Yogya Mall Brebes Regency. The population in this study was consumers of Pepsodent toothpaste in Yogya Mall. The number of samples used in this study was 136 respondents. Data collection was carried out by distributing questionnaires to Pepsodent toothpaste consumers at Yogya Mall. The analytical techniques used in this study are validity tests, reliability tests, classical assumption tests and multiple regression tests. The results showed that the variables of consumer satisfaction and service quality did not have a positive effect on repurchase interest, on the contrary, celebrity endorser variables and brand trust had a positive and significant effect on repurchase interest. Simultaneously, customer satisfaction, service quality, celebrity endorsers and brand trust affect the interest in repurchasing Pepsodent toothpaste at Yogya Mall Brebes Regency.